2020
DOI: 10.3390/agriculture10120650
|View full text |Cite
|
Sign up to set email alerts
|

Root Growth of Hordeum vulgare and Vicia faba in the Biopore Sheath

Abstract: Biopores provide nutrients from root debris and earthworm casts. Inside large biopores, root function is limited due to the lack of root–soil contact. However, the immediate surroundings of biopores may hold a key function as “hotspots” for root growth in the subsoil. To date, sufficient quantitative information on the distribution of roots and nutrients around biopores is missing. In this field study, the biopore sheath was sampled at distances of 0–2, 2–4, 4–8, and 8–12 mm from the surface of the pore wall. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Petzoldt and Kautz (2021) observed that the utilization of oilseed rape roots to the soil near the biopores was greater than that of faba bean, possibly due to their various rooting behavior. Moreover, Petzoldt et al (2020) found that the root length density of spring barley was 7.4 times higher than that of faba bean at a distance of 0-2 mm from the biopores. This may be due to the thicker and less morphological plasticity of faba bean roots (Athmann et al, 2019;Li et al, 2014;Materechera et al, 1991;Zhang et al, 2016), resulting in fewer roots in the biopore sheath.…”
Section: Root-biopore Interaction Is Affected By Crop Speciesmentioning
confidence: 97%
See 2 more Smart Citations
“…Petzoldt and Kautz (2021) observed that the utilization of oilseed rape roots to the soil near the biopores was greater than that of faba bean, possibly due to their various rooting behavior. Moreover, Petzoldt et al (2020) found that the root length density of spring barley was 7.4 times higher than that of faba bean at a distance of 0-2 mm from the biopores. This may be due to the thicker and less morphological plasticity of faba bean roots (Athmann et al, 2019;Li et al, 2014;Materechera et al, 1991;Zhang et al, 2016), resulting in fewer roots in the biopore sheath.…”
Section: Root-biopore Interaction Is Affected By Crop Speciesmentioning
confidence: 97%
“…The entry of fine roots into the biopore sheath is also significant for nutrient absorption in subsoil (Petzoldt et al, 2020). Petzoldt and Kautz (2021) found that oilseed rape roots could grow toward the biopore sheath due to N enrichment in the biopore sheath.…”
Section: Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…After finishing the pH measurements, soil samples were taken in a soil depth of 25-35 cm in three lateral distances from pore surface: 0-2, 2-4 and 4-8 mm for analyzing the total content of C and N (C t , N t ). The scraping sampling device and the proceeding of the samples, as well as the measurement of the elements are described in detail in Petzoldt et al 2020.…”
Section: Determination Of Total C-and N-contentmentioning
confidence: 99%
“…Root growth in untilled deeper soil layers can be facilitated by physical access paths through biopores (Passioura 1991;Logsdon and Linden 1992). Biopore surroundings provide elevated nutrient concentrations, particularly in the first two millimeters of the sheath due to earthworm linings and root debris (Lavelle 1988;Athmann et al 2017;Petzoldt et al 2020). Generally, crops can respond to different nutrient availabilities in their root growing environment by changing their metabolic activity as reviewed by, e.g.…”
Section: Introductionmentioning
confidence: 99%